Understanding the Processes of how Small and Medium Enterprises derive Value from Business Intelligence and Analytics - Wee, Mak; Scheepers, Helana; Tian, Xuemei (Australasian Journal of Information Systems, 2022)
This paper provides an in-depth study of how small and medium enterprises (SMEs) use business intelligence and analytics (BI&A) to derive business value and why so many SMEs fail to do so. A qualitative research approach based on semi-structured interviews with five SMEs in Australia was applied with the goal is to understand the process in which SMEs adopt BI&A to derive business value. This involved exploring how owners and managers lead their employees in using data and analytical processes to derive insights to make business decisions. The findings suggest that SMEs which adopt BI&A use a short and simple six-step iterative BI&A process to derive insights for business process application. In addition to the short process, a longer three phase process has been identified which progresses SMEs from solving operational issues to strategic challenges. The resulting short and long BI&A implementation process framework provides a progressive pathway for SME owners and managers to initiate and lead BI&A transformation in their SMEs to derive greater business value. The process model considers dimensions of data, analysis, business process change, social influence, level of information use and financial returns.